Influence of dentistry procedures on masticatory function of dentate patients - Lucas do Nascimento Tavares (Brazilian Journal of Oral Sciences, 2017)
Aim: Evaluate the masticatory performance in patients with different clinical situations: patients with natural dentition without restorative and/or orthodontic intervention (Group CG) and patients with restorations and/or orthodontic intervention (Group TG). Subjects received instruction before the experiment, related to masticatory movements. Methods: Three capsules containing the granules were delivered separately to chew for 20 seconds each, controlled by the examiner. One capsule was chewed for 20 seconds only on the left side; the second capsule was chewed for 20 seconds only on the right side; and the third capsule was chewed for 20 seconds to simulate each patient’s mastication. The mean data and standard deviation of masticatory function of each patient was calculated. Results: The results obtained in this study showed that there were no statistically significant differences (P < 0.05) between both tested groups (0.0320 ± 0.00716, 0.0436 ± 0.00974). Conclusions: Patients who were submitted to orthodontic and/or restorative procedures, with balanced occlusion could be used as a control group, making easier the patient recruitment. Clinicians and researchers on masticatory performance evaluation could apply the colorimetric method. The colorimetric method was a standardize method, effective and easy to execute.